Does access to free health insurance crowd-out private transfers? Evidence from Mexico's Seguro Popular - Pedro P. Orraca-Romano (Latin American Economic Review, 2015)
This study examines whether Seguro Popular, a free-of-charge publicly provided health insurance program for otherwise uninsured households, crowded-out private transfers in Mexico. Using data from the National Household Income and Expenditure Survey, the effects of Seguro Popular are identified using the spatial variation in the program's coverage induced by its sequential roll-out throughout Mexico. The results show that Seguro Popular reduced on average a household's probability of receiving private transfers by 5.55 % points. This finding appears to be driven by domestic private transfers, since the program's effects are only statistically significant for private transfers originating within Mexico. In addition, Seguro Popular had a weak and not statistically significant negative effect on the amount of private transfers received. Failure to take into account possible changes in private behaviour induced by Seguro Popular may overstate the program's potential benefits or distributional impacts.
Keywords: I13; I18; I38; 330; Public health insurance; Crowding-out; Private transfers; Mexico; Seguro Popular